Congratulations MScTILS Graduates - Noor Raha, Mohd Radzuan (2022)
Universiti Malaysia Pahang (UMP) celebrated the 16th Convocation Ceremony from 6 August to 9 August 2022 in the Sports Hall, UMP Gambang Campus. A total of 4,083 graduates for 2021 comprising doctoral and master’s graduands (280), bachelor’s (2,235) and diploma graduands (506), and UMP Advanced graduands (1,062) received degrees and diplomas.